Strains of Lactobacillus plantarum in Grape Must are also Present in the Intestinal Tract of Vinegar Flies - Groenewald, W.H.; van Reenen, C.A.; Dicks, L.M.T. (South African Journal of Enology and Viticulture, 2017)
Twenty-one lactic acid bacteria isolated from the intestinal tract of Drosophila simulans Stuvervant and nine from Merlot noir grapes were identified as L. plantarum by PCR with species-specific primers and 16S rDNA sequencing. The 30 isolates grouped into four clusters based on RAPD-PCR banding patterns, suggesting that they belong to at least four genotypic groups. Thirteen isolates from grape must and five from the flies yielded identical RAPDPCR banding patterns and grouped into one cluster, suggesting that they are descendants from the same strain. Concluded from these results, L. plantarum (or at least descendants from a specific strain) has the ability to use vinegar flies as a host and vector to infect grape must. Further research is needed to determine the role of this specific strain in wine fermentations.